Instability of a thin conducting foil accelerated by a finite wavelength intense laser - B Eliasson (New Journal of Physics, 2015)
We derive a theoretical model for the Rayleigh–Taylor (RT)‐like instability for a thin foil accelerated by an intense laser, taking into account finite-wavelength effects in the laser wave field. These finite-wavelength effects lead to the diffraction of the electromagnetic wave off the periodic structures arising from the instability of the foil, which significantly modifies the growth rate of the RT-like instability when the perturbations on the foil have wavenumbers comparable to or larger than the laser wavenumber. In particular, the growth rate has a local maximum at a perturbation wavenumber approximately equal to the laser wavenumber. The standard RT instability, arising from a pressure difference between the two sides of a foil, is approximately recovered for perturbation wavenumbers smaller than the laser wavenumber. Differences in the results for circular and linear polarization of the laser light are pointed out. The model has significance for radiation pressure acceleration of thin foils, where RT-like instabilities are significant obstacles.